Deconstructing Underlying Assumptions about Trafficked Minors and Children - Norwood, Jeremy (Anti-Trafficking Review, 2019)
In Trafficked Children and Youth in the United States: Reimagining Survivors, Elżbieta M. Goździak (2016) not only explores the experiences of children and youth who have been exploited by their traffickers, but she also addresses the system in the United States that seeks to intervene and assist them. In order to understand this apparent process of victimisation, Goździak articulates the need to deconstruct popular conceptions of human trafficking itself, particularly as she seeks to give voice to the survivors and lend credibility to the trauma that they have endured. In order to accomplish this larger purpose, Goździak begins by identifying service providers which assist in the aftercare process for those impacted by human trafficking. She then spends time visiting these aftercare facilities, listening to the children and youth survivors of human trafficking, and documenting their stories and life circumstances.